(untitled) (International Journal of Nursing Education, 2020)
Because of the physical changes at the time of puberty, children in the age group of 10 to 19 show moreinterest to know about sex and sexuality. With the thinking of what father and brother will think of me if I askdoubts about the changes, they bury their doubts inside themselves. They do not get correct answer about thechanges in the anatomy and sexuality. In such situations, they talk with other children in the same age groupwho are also facing the same situation. When they are unable to collect more knowledge, they become leanerto know about the opposite sex. Most of them do experiments and land up with worsened situation. They cantake care of themselves in a healthy and adaptive way if we provide correct and enough knowledge about thechanges that happens in their body at different ages and sexuality. If we hesitate to provide correct and mustknowledge to the children, they will be in a confused state and is ashamed of not having proper knowledgeabout their own body. So the condition can be more vulnerable.Because of the lack of correct knowledge about puberty, the adolescent boys may feel more anxiety, moretension, sometimes fear, nervousness, becomes restlessness and extremely stressed. The lack of correctknowledge can lead to a situation that they won’t be able to manage the situation. In that case, they try drugs,drinks and smoking. Ultimately this will leads to bullying, lying, drunk driving, rebellious behavior, bodyissues and mental health issues. Other than these, they may feel physical symptoms like nausea, vomiting,headache, stomach ache etc. They also have the right to enjoy their life in a healthy manner.